Evaluation of the care network for women in situations of domestic violence - Machado, Natália Moreira; Braz, Milena Marcintha Alves (Revista Aval, 2025)
This study evaluates the work developed by the network of assistance to women in situations of domestic violence in São Gonçalo do Amarante-CE (SGA-CE) based on the National Policy for Combating Violence against Women and anchored in an evaluation perspective guided by critical-dialectic theoretical-methodological approach by Maria Ozanira Silva e Silva. To achieve this, we used bibliographical, field and documentary research, as well as interviews and questionnaires, involving different subjects. Thus, it was observed that the municipality has made efforts to coordinate the protection and assistance network for women victims of violence, however there are still challenges to be overcome.